2012
DOI: 10.1097/shk.0b013e31825b1717
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Small-Bowel Barrier Integrity in the Presence of Lumenal Pancreatic Digestive Enzymes Leads to Circulatory Shock

Abstract: In bowel ischemia, impaired mucosal integrity may allow intestinal pancreatic enzyme products to become systemic and precipitate irreversible shock and death. This can be attenuated by pancreatic enzyme inhibition in the small bowel lumen. It is unresolved, however, whether ischemically-mediated mucosal disruption is the key event allowing pancreatic enzyme products systemic access, and whether intestinal digestive enzyme activity in concert with increased mucosal permeability leads to shock in the absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 26 publications
0
25
0
1
Order By: Relevance
“…Thus, one advantage of the pancreatic duct ligation model is that it eliminates luminal pancreatic enzymes and serves as a proof-of-principle model testing the role of mucus disruption on pancreatitis-induced gut permeability changes. Our results also suggest that pancreatic proteases are not likely necessary for the initiation of the mucus changes observed in early acute pancreatitis, although their presence could potentiate damage to the oxidant-modified mucus layer (33). …”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Thus, one advantage of the pancreatic duct ligation model is that it eliminates luminal pancreatic enzymes and serves as a proof-of-principle model testing the role of mucus disruption on pancreatitis-induced gut permeability changes. Our results also suggest that pancreatic proteases are not likely necessary for the initiation of the mucus changes observed in early acute pancreatitis, although their presence could potentiate damage to the oxidant-modified mucus layer (33). …”
Section: Discussionmentioning
confidence: 69%
“…This is in contrast to toxin-induced models of pancreatitis wherein pancreatic proteases are secreted into the gut lumen and morphologic evidence of gut injury is more pronounced (27, 29-31). The potentially toxic role of luminal pancreatic proteases is supported by studies showing that the ischemic or stressed gut is susceptible to autodigestion by luminal digestive enzymes if they come into direct contact with the epithelial barrier (10, 32, 33). Thus, the fact that the duct ligation model prevents pancreatic enzymes from reaching the gut lumen could help explain the lack of microscopic morphologic evidence of gut injury.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, the presence of luminal pancreatic proteases only led to increased gut morphological injury and increased permeability when the mucus layer was impaired. Recent work from Schmid-Schonbein's group has also demonstrated that the intestinal mucus layer serves to limit digestive enzymes from reaching the gut epithelial layer in both normal animals and in animals subjected to a gut ischemia-reperfusion insult (5,17). In conclusion, decreases in splanchnic blood flow resulting in a gut ischemia-reperfusion insult appear to be necessary components of gut injury and loss of barrier function after T/HS, as well as in other model systems associated with gut ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…with mucolytic N-acetylcysteine treatment) allows digestive enzymes to enter the intestinal wall, a process that is followed by severe damage to the intestinal mucosa (20) and may lead to death even in the absence of any other systemic challenge (19). …”
Section: Breakdown Of the Mucosal Barrier: A Hallmark For Shockmentioning
confidence: 99%